English language assessment in business context: a case study - Kobayashi, Eliana (2019)
Although English language is considered an essential requirement to find a position in the Brazilian work market, little do we know about what proficiency level is expected from workers by companies and how language assessment occurs at work. This investigation was developed in an automation company located in São Paulo metropolitan area. It is a case study which aimed to better understand the language use expectations and analyze the assessment process to identify: the assessment tools used in the company, its language view and if the assessment process meets the company’s language use expectations. This study uses questionnaires, interviews and documents analysis for data collection and triangulation of sources. The company is a place where English is used in daily tasks due to international partnerships and taught in an in-company course. The results show a mismatch between the proficiency and achievement tests applied in the company and its language view. In addition English language is a gatekeeper in recruitment process only for some positions. The language use expectations for workers vary according to their position and department but are not assessed likewise.